W. Africa : : Visits, Major H. Vischer - Vischer, Hanns; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1938)
Colonial Office file concerning Hanns Vischer's visits to various locations in West Africa to assess and report on schools and other educational matters in the colonies